Research productivity on science learning: a bibliometric study international from 2013 to 2023 - Widayanti, Widayanti; Istiyono, Edi; Haryanto, Haryanto; Retnawati, Heri; Sinensis, Arini Rosa; Bujuri, Dian Andesta (Institute of Advanced Engineering and Science, 2024)
This research focuses on evaluating research productivity in the realm of science learning using various bibliometric indicators. A total of 4,942 scientific publications were taken from the Scopus database from the period 2013–2023, applying related keyword searches. The result is presented in graphical form. Studies also use VOSviewer and Biblioshiny tools through R to evaluate network visualizations and find the most prolific authors, number of publications and citations, country representatives, organizational and university contributions, publishers, and frequently appearing words. The results reveal a growing trend in total publications in the past 10 years of research. Out of a total of 4,942 scientific publications, NA NA is one of the most prolific authors. The USA and China are the most productive countries when it comes to publishing research in the field. The University of California, National Taiwan Normal University, and Purdue University are reported to be the top three productive organizations in the field of science learning. The study also looked at collaboration and cooperation between authors, countries, and organizations in visualization analysis. The results of the word that often appears are reported to be that science, education, learning, and effects have maximum link strength.